Debata parlamentarna nad wyłonieniem składu Komisji Wojskowej w grudniu 1788 r. - Szczygielski, Wojciech (Przegląd Nauk Historycznych, 2011)
Thanks to electing its members (on 22nd December 1788) the Military Commission took over the real power over the army. Overthrown during the parliamentary session of 3rd November 1788, the Military Department of the Permanent Council finally stopped functioning. During the December debate the deputies, who slightly outnumbered the senators, tried to increase their majority in the Seym. In the confederated Seym the votes of deputies and the votes of senators carried the same weight and consequently the result of parliamentary voting depended on the overall counting of all the votes. That is why the problem of deputies’ representation in the Seym was a matter of great significance. In order not to decrease the number of deputies it was decided that the current deputies would not become the members of the Commission (there was a fear that the deputies involved in the work of the Commission might neglect their duties as members of Parliament). At the same time the gentry aimed at increasing their majority in the Seym by excluding from the parliamentary debates those senators who would be elected for the Commission. However, this initiative failed due to the strong opposition of the senators. Instead, the senators suggested that the deputies’ majority in the Seym should be increased directly by increasing the number of deputy seats. The deputies accepted this proposal. For the time being it was not put into practice yet. However, the December debate lay foundations for the compromise between the gentry and the senators concerning preserving the senators’ legislative rights within the framework of the “two-chamber” Seym.